PENERAPAN BUDAYA ORGANISASI (STUDI KASUS PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG DAGO BANDUNG) - Arcaya Yudha; Herbasuki Nurcahyanto; Nina Widowati (Journal of Public Policy and Management Review, 2013)
BRI Branch Dago Office is the only one that has a priority service functions branch  office in Bandung that operate under the supervision of the Office of the BRI Bandung. Branch office is a BRI branch office that implement functions to raise funds from the  public in the form of savings and channel them to the public in the form of credit and or other forms in order to improve the living standard of the people, which is responsible  to the Regional Office. This study aims to identify and analyze models of organizational culture and the  implementation of organizational culture values in PT. Bank Rakyat Indonesia branch  Dago Bandung so as to know what needs to be repaired and maintained. Model of organizational culture and the implementation of the cultural values of  the organization are identified and analyzed  from the organizational structure, human  resource management policies, integrity,  professionalism, customer satisfaction,  exemplary and respect for human resource. In this study, researchers used a purposive  technique. Data collection method used is in-depth interviews and documentation  techniques. This study shows that the model of organizational culture and the  implementation of organizational culture values indicate there is still a problem in  terms of integrity and professionalism, integrity is still considered less value because of  the work period is too short for contract workers, so that the organizational culture is  not well understood by contract workers who are at the forefront of service. professionalism that most of the cutting edge services are contract workers who were  given a short training, a result is they lack an understanding of the products of the Bank Rakyat Indonesia branch Dago